Utility of Non-invasive Cardiac Imaging Assessment in Coronavirus Disease 2019 - Hothi, Sandeep S.; Jiang, Jin; Steeds, Richard P.; Moody, William E. (Frontiers in Cardiovascular Medicine, 2021)
Coronavirus disease-2019 was initially regarded as a disease of the lungs, manifest as an acute respiratory illness and pneumonia, although more recently cardiac complications have been well characterised. Serological cardiac biomarkers have been used to define acute myocardial injury, with significant elevation of cardiac troponin associated with poor prognosis. Accordingly, 20-25% patients with acute myocardial injury (as defined by an elevated cardiac troponin greater than the 99th percentile) have clinical signs of heart failure and increased mortality. An important outstanding clinical question is how best to detect the extent and nature of cardiac involvement in COVID-19. Non-invasive cardiac imaging has a well-established role in assessing cardiac structure and function in a wide range of cardiac diseases. It offers the potential to differentiate between direct and indirect COVID-19 effects upon the heart, providing incremental diagnostic and prognostic utility beyond the information yielded by elevated cardiac biomarkers in isolation. This review focuses on the non-invasive assessment of cardiac involvement in COVID-19. We acknowledge that this is a new disease, and that knowledge will continue to evolve with time. Nevertheless, there is a need to consolidate what is currently known to help inform clinical and research strategies.